Marketing for Sustainable Tourism 2019
DOI: 10.4324/9780203711668-3
|View full text |Cite
|
Sign up to set email alerts
|

Social marketing, sustainable tourism, and small/medium size tourism enterprises: challenges and opportunities for changing guest behaviour

Abstract: This paper investigates the impact on the guest experience of initiatives promoting water efficient behaviour in small--/ medium--sized enterprises (SMTEs) offering tourism accommodation. Interviews with 16 SMTE managers revealed businesses were unable to incorporate many initiatives previously examined in the literature due to the small size of their businesses. In the interviews, however, they contributed three new ideas not previously examined in existing sustainable tourism dialogues. A subsequent question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Earlier research has shown that sustainability messages, even from sustainability award-winning firms, are not persuasive (Villarino & Font, 2015). This has been deemed to stem from their lack of belief that their messages will be effective (Borden, Coles, & Shaw, 2017;Font, Elgammal, & Lamond, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that sustainability messages, even from sustainability award-winning firms, are not persuasive (Villarino & Font, 2015). This has been deemed to stem from their lack of belief that their messages will be effective (Borden, Coles, & Shaw, 2017;Font, Elgammal, & Lamond, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Four initiatives were highly prioritized by the panel: “remove barriers to change,” “initial welcome,” “incentives,” and “green ambassadors.” However, of these four initiatives, “incentives” scored the lowest for agreement (only 63.2%) that it would change behavior. Additionally, Borden, Coles and Shaw (2017) report that incentives are not always a possibility for smaller tourism accommodation firms and may therefore not be a viable option for intervention. Interestingly, “feedback cards” were highly supported by guests in earlier research stages as reported by Borden, Coles and Shaw (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Borden, Coles and Shaw (2017) report that incentives are not always a possibility for smaller tourism accommodation firms and may therefore not be a viable option for intervention. Interestingly, “feedback cards” were highly supported by guests in earlier research stages as reported by Borden, Coles and Shaw (2017). However, the Delphi panel felt they were likely to be completed after the guest experience and therefore have little effect on their behavior while staying in the accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research was conducted in two stages: a survey of patrons and subsequent experimental interventions. As identified by Carins, Rundle-Thiele, and Fidock (2016) and Borden, Coles, and Shaw (2017), social marketing campaigns which rely solely on survey data may be more prone to social desirability bias and the well-documented attitude–behavior gap (Kollmuss & Agyeman, 2002). Social desirability bias refers to the phenomenon of participants responding to a surveyor in a manner in which they believe the researcher would desire.…”
Section: Methodsmentioning
confidence: 99%